Micro-optical element with high bonding strength between glass substrate and microstructure layer
By using a glass substrate with a high NBO quantity and optimizing its geometric surface characteristics, the problem of insufficient bonding strength between the glass substrate and the microstructure layer in the prior art is solved, and high stability and good bonding strength are achieved.
Patent Information
- Application Number
- CN202010921307.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-06
- Filing Date
- 2020-09-04
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-09-04
AI Technical Summary
The prior art is difficult to economically provide micro-optical elements with glass substrates and microstructure layers with high bonding strength, especially with the challenge of peeling between glass substrates and microstructure layers.
The bond strength to the microstructure layer is improved by using a glass substrate with a high amount of non-bridge oxygen (NBO) and optimizing its geometric surface characteristics such as total thickness variation (TTV), thickness tolerance, warpage and surface roughness.
High bonding strength between the glass substrate and the microstructure layer is achieved, and the stability is good in high temperature and high humidity environments, and the bonding strength degradation is less than 60%.
Smart Images

Figure CN112462454B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to micro-optical elements in the field of 3D imaging and sensing, in particular wafer-level optical devices. In particular, the present invention relates to a micro-optical element having a glass substrate and a micro-structure layer bonded to each other and having high stability due to the tight bonding between the glass substrate and the micro-structure layer. Background Art
[0002] For a micro-optical element having a glass substrate and a micro-structure layer, the bonding strength between the glass substrate and the micro-structure layer is a key requirement, because the peeling of the micro-structure layer from the glass substrate has always been difficult and has always been a concern.
[0003] In order to reliably obtain a bonding surface with high bonding strength between a glass substrate and a microstructure layer, Koji et al. proposed a Fresnel lens made of a thermoplastic polymer composition in EP 3093139 A1, the thermoplastic polymer composition includes an acrylic block copolymer (A) and an acrylic resin (B), wherein the acrylic block copolymer (A) is an acrylic block polymer having at least one structure in the molecule, in which a polymer block (a2) mainly composed of methacrylate units is bonded to each end of a polymer block (a1) mainly composed of acrylate units. The thermoplastic polymer component can be reliably bonded to a silane coupling agent applied to a glass substrate. However, the synthesis of the acrylic block copolymer (A) is time-consuming and laborious, and the production cost is expensive, which is uneconomical.
[0004] Therefore, in the field of micro-optics, there is still a need to provide micro-optical elements between a glass substrate and a microstructure layer in a labor-saving and cost-saving manner. Summary of the invention
[0005] An object of the present application is to provide a micro-optical element having a glass substrate and a micro-structure layer bonded to each other and having high stability due to close bonding between the glass substrate and the micro-structure layer.
[0006] This object is achieved by a glass substrate with a specific glass composition and optimized geometric surface properties as claimed in the independent claims. Glass components with high non-bridge oxygen (NBO) or active oxygen will generate OH-, which can improve the bonding strength with the microstructure layer. The glass substrate has a suitable total thickness variation (TTV), thickness tolerance and warpage, which are conducive to obtaining a high bonding strength with a consistent microstructure layer. High TTV and warpage are not conducive to obtaining a stable microstructured polymer layer production process because the thickness of the polymer is affected by the TTV and warpage of the glass. On the other hand, the microstructure layer is also affected by the roughness of the glass during spin coating, spraying, deposition or printing. Low glass roughness facilitates the coating of the polymer on the glass, which is beneficial to the formation of a consistent microstructure layer.
[0007] According to one aspect of the present invention, a micro-optical element comprises: a glass substrate and a microstructure layer. The glass substrate has a thickness of t≤1500μm, preferably t≤1200μm, and more preferably t≤1100μm. Other thicknesses of ≤900μm, 800μm, 700μm, 500μm, 400μm, 300μm, 200μm, and 100μm may also be used. However, the glass thickness in this patent is not limited to the above thickness. The microstructure layer formed by a polymer is embossed on the glass substrate. Through optical design, the microstructure has an optical function. The microstructure can be any structure (e.g., hemisphere, multi-order, circular, square) that can produce a refractive effect or a diffraction effect in an optical device according to optical design. The glass substrate exhibits a glue contact angle θg of less than 35°, preferably less than 25°, and more preferably less than 15°. The bonding strength P is defined as the minimum pressure that can separate the microstructure layer from the glass substrate. The bonding strength between the glass substrate and the microstructure layer is greater than 0.5 MPa, preferably greater than 1 MPa, and more preferably greater than 1.5 MPa. After 1000 cycles at a temperature of 85° C. and a humidity of 85%, the degradation of the bonding strength is less than 60%, preferably less than 50%, and more preferably less than 40%.
[0008] In another preferred embodiment, the glass substrate has a refractive index n in the range of 1.4 to 2.5, preferably in the range of 1.41 to 2.1, preferably in the range of 1.42 to 2.0, preferably in the range of 1.45 to 1.9, particularly preferably in the range of 1.45-1.8, more preferably in the range of 1.45-1.7, most preferably in the range of 1.45-1.6. d In this case, the glass substrate can be used for optical applications. In one embodiment, the refractive index n between the glass substrate and the microstructure layer is d The difference Δn d <0.5.
[0009] In a preferred embodiment, the glass substrate has a non-bridging oxygen NBO number of NBO>0.3, preferably NBO>0.5, more preferably NBO>1, particularly preferably NBO>1.5, and most preferably NBO>2, wherein NBO=(R2O+R'O) / (P2O5+Al2O3+B2O3+TiO2+ZrO2). The ratio X=(R2O+R'O-P2O5-Al2O3-B2O3) / (SiO2+P2O5+Al2O3+B2O3) is greater than -0.2, preferably greater than 0, and more preferably greater than 0.2. In the present invention, R is an alkali metal, including Li, Na, K; R' is an alkaline earth metal, including Mg, Ca, Ba.
[0010] In another preferred embodiment, the glass comprises the following oxide-based components in mol %:
[0011]
[0012] In a preferred embodiment, the glass substrate has a surface tension σ of ≥100 dyn / cm at 1300° C., particularly preferably σ ≥120 dyn / cm at 1300° C., and more preferably σ ≥140 dyn / cm at 1300° C. Higher surface tension leads to a smaller water / glue contact angle, which increases the bonding strength between the glass and the microstructure layer.
[0013] The total thickness variation (TTV) is the difference between the minimum and maximum values of the thickness throughout the glass. TTV is identified in a scan pattern or by taking a series of point measurements on the glass. In another preferred embodiment, the glass substrate has a total thickness variation (TTV) of TTV ≤ 40 μm, preferably TTV ≤ 30 μm, more preferably TTV ≤ 20 μm, particularly preferably TTV ≤ 10 μm, and most likely TTV ≤ 5 μm. In this case, due to the low TTV, the bond strength between the glass surface and the microstructure layer is uniform and improved.
[0014] In another preferred embodiment, the glass substrate has a thickness tolerance δ of δ≤80 μm, preferably δ≤50 μm, more preferably δ≤20 μm, further preferably δ≤10 μm, particularly preferably δ≤5 μm, and most preferably δ≤2 μm.
[0015] In another preferred embodiment, the glass substrate exhibits a warp of ≤500 μm, preferably ≤100 μm, more preferably ≤80 μm, most preferably ≤50 μm. In this case, the glass substrate may be substantially parallel to the microstructure layer, which may improve uniform bonding strength between the glass substrate and the microstructure layer.
[0016] In another preferred embodiment, the ratio of TTV (total thickness variation) to thickness of the glass substrate is less than 10%, preferably less than 8%, and more preferably less than 5%.
[0017] In another preferred embodiment, the glass substrate has a surface roughness Ra of ≤20 nm, preferably Ra ≤10 nm, and more preferably Ra ≤5 nm. In this case, due to the low surface roughness, an empty adhesive layer between the glass substrate and the microstructure layer can be avoided, and a uniform thickness of the adhesive layer can be achieved. Low glass roughness is conducive to the coating of the polymer on the glass and the formation of a consistent microstructure layer. On the other hand, high roughness will reduce the optical performance.
[0018] In another preferred embodiment, the glass substrate shows a transmittance of T≥90%, preferably T≥91%, and more preferably T≥92% at a wavelength of 400 to 1500 nm. The glass substrate may be coated. By applying, for example, an anti-refraction coating, the transmittance may be T≥95%, and more preferably T≥99%.
[0019] In another preferred embodiment, the glass substrate exhibits a coefficient of thermal expansion of CTE 20-300℃ ≤15×10 -6 / K, preferably CTE 20-300℃ ≤10×10 -6 / K. In addition, the CTE of the glass substrate 玻璃 CTE of the microstructure layer 聚合物 CTE 聚合物 / CTE 玻璃 ≤100, preferred CTE 聚合物 / CTE 玻璃 ≤80.
[0020] In another preferred embodiment, the refractive index n between the glass substrate and the microstructure layer is d The difference Δn d ≤0.5.
[0021] In this embodiment, the diffractive optical element DOE is designed for applications with lasers and high-power lasers. It is used as a multi-point beam splitter in beam shaping and beam profile modification, and these elements offer unlimited possibilities in different application fields. DOE can be used for optical applications, especially diffractive optical elements or refractive optical elements, all of which can be used in the field of 3D imaging and sensing or in fields that require depth detection or recognition functions, such as entertainment, gesture recognition, tracking of hand joints, and facial recognition systems, augmented reality, and virtual reality.
[0022] In another preferred embodiment, the glass substrate is made of a glass selected from the group consisting of silicate glass, borosilicate glass, aluminosilicate glass, aluminoborosilicate glass, soda-lime glass and lithium aluminosilicate glass (LAS).
[0023] In another preferred embodiment, the microstructure layer is composed of a group of polymers selected from epoxy resins and acrylic resins. The polymer may contain some inorganic materials (such as SiO2) to increase the refractive index of the polymer. However, the polymer is not limited to the above polymers. Any polymer that can form the desired microstructure can be used to make the microstructure layer.
[0024] In another aspect of the present invention, a method for manufacturing the above-mentioned micro-optical element is provided. The method comprises the following steps:
[0025] - providing a glass substrate, the thickness of the glass substrate is t≤1500 μm, preferably t≤1200 μm, more preferably t≤1100 μm, wherein the total thickness variation of the glass substrate is TTV≤40 μm, preferably TTV≤30 μm, more preferably TTV≤20 μm, particularly preferably TTV≤10 μm, most preferably TTV≤5 μm; the thickness tolerance of the glass substrate is δ≤80 μm, preferably δ≤50 μm, more preferably δ≤20 μm, further preferably δ≤10 μm, particularly preferably δ≤5 μm, most preferably δ≤2 μm,
[0026] – Applying a microstructured polymer layer on a glass substrate, where the microstructure profile can be a periodic structure of pyramids, circles, triangles, squares, sawtooths, metasurfaces with two-phase energy levels, asymmetric geometric phase optical elements and other infinite optical elements according to optical design.
[0027] The application of microstructured polymer layers on glass substrates involves three main process steps: origination, replication and pattern transfer, namely:
[0028] (a) A polymer is deposited on a substrate and a UV-transparent template is placed on top;
[0029] (b) pressing the template into the polymer and curing the polymer by irradiating the template with ultraviolet light or heating the template; and
[0030] (c) releasing the template, leaving behind a cured polymer with the imprinted features to form a microstructure layer, wherein the template may be made of metal, quartz or other suitable material, and the polymer may be cured by heat, UV flash or other suitable method.
[0031] In another preferred embodiment, the microstructure layer may alternatively be applied by printing, spin coating, spray coating or deposition and methods not limited thereto.
[0032] In another preferred embodiment, the microstructure layer can be cured by thermal heating or similar methods.
[0033] In another preferred embodiment, the microstructure layer may be applied to both sides of the glass substrate.
[0034] In the present invention, the glass has a large number of NBOs, and therefore, the glass has more negatively charged oxygen (so-called "active oxygen"). It has been found that a large number of NBOs or more active oxygen can produce a highly active glass surface, which can increase the wettability of the glass surface and reduce the water / glue contact angle. Good glass surface wettability and a small water / glue contact angle are beneficial to increase the bonding strength between glass and glue (i.e., glue layer), thereby increasing stability.
[0035] The micro-optical elements according to the present invention can be used in diffractive optical elements, refractive lenses, mirrors, prisms, GRIN lenses, hybrid elements, diffusers in 3D imaging / sensors, augmented reality, virtual reality, cameras, automated manufacturing systems, mobile communications. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 shows a simplified view of a micro-optical element having a glass substrate and a microstructure layer;
[0037] Figure 2 A sampling curve showing the relationship between contact angle and NBO value;
[0038] Figure 3 A sampling curve showing the relationship between contact angle and X value;
[0039] 4A to 4C show the glue contact angle of the glass according to the present invention;
[0040] FIG. 5A to FIG. 5B A schematic diagram showing bonding on a glass surface according to the prior art and the present invention is shown;
[0041] Figure 6 A schematic diagram showing activated glass and chemical bonding to a microstructure layer according to the present invention; and
[0042] Figure 7 A schematic diagram showing the bonding strength versus contact angle is shown. DETAILED DESCRIPTION
[0043] The objects, features and advantages of the present invention are explained in more detail through the examples and embodiments described below with reference to the accompanying drawings.
[0044] Figure 1 A simplified view of a micro-optical element 1 according to the present invention having a glass substrate 2 and a microstructure layer 3 directly bonded together is shown. The microstructure layer 3 is imprinted on the glass substrate 2, which has an optical structure on top thereof, such as a lens 4 in this embodiment. In the present invention, the optical structure is not limited to the lens 4, and may include other optical elements, such as a sensor. For the microstructure layer 3, a polymer including an epoxy resin as a UV curing imprint material (e.g., a glue OM 614) and acrylic resin. However, the polymer is not limited to epoxy resin and acrylic resin, but also includes other polymers having adhesive properties.
[0045] The glass substrate 2 is made of ultra-thin glass selected from the group consisting of silicate glass, borosilicate glass, aluminosilicate glass, borosilicate aluminum glass, soda-lime glass and lithium aluminum silicate glass (LAS). The ultra-thin glass according to the present invention can be manufactured by methods such as down-drawing, up-drawing, float or overflow melting.
[0046] The thickness of the glass substrate 2 is t≤800 μm, preferably t≤500 μm, more preferably t≤100 μm. The glue contact angle θg of the glass substrate 2 is less than 5°, preferably less than 40°, more preferably less than 30°, and most preferably less than 15°. In this case, since the glue contact angle θg of the glass substrate 2 is small, this is beneficial to the bonding strength between the glass substrate and the microstructure layer 3, and improves reliability and stability.
[0047] It has been found that the glue contact angle θg of the glass substrate is determined by the specific parameters of the glass. In short, as described above, high non-bridging oxygen (NBO) can produce more negatively charged oxygen ("active oxygen"), and more NBO or more active oxygen can produce a highly active glass surface, thereby increasing the wettability of the glass surface and reducing the water / glue contact angle. Good glass surface wettability and low water / glue contact angle help to improve the bonding strength between glass and glue (such as microstructure layer 3 in this case), thereby increasing stability. In the present invention, NBO is defined by the following formula (1).
[0048] NBO=(R2O+R'O) / (P2O5+Al2O3+B2O3+TiO2+ZrO2) (1)
[0049] Wherein R is an alkali metal, including Li, Na, and K; R' is an alkaline earth metal, including Mg, Ca, and Ba.
[0050] In the present invention, the glass substrate has a certain amount of NBO. A large amount of NBO can improve the performance, reliability and bonding strength of the bond between the glass substrate 2 and the microstructure layer 3. Larger NBO can attract more OH on the glass surface, and more OH can produce better liquid wettability, thereby improving the bonding strength between the glass substrate 2 and the microstructure layer 3. In addition, a large amount of NBO can reduce the water / glue contact angle, and a lower contact angle can produce better bonding strength. It has been found that if the value of NBO is greater than 1, it means that there is enough modifier, which provides NBO in the glass substrate, and the glass structure is loose. If the value of NBO is less than or equal to 1, it means that the glass modifier in the glass substrate is insufficient and the glass structure is dense. In the present invention, the NBO value of the glass substrate is greater than 0.3, preferably greater than 0.5, more preferably greater than 1, particularly preferably greater than 1.5, and most preferably greater than 2.
[0051] In addition, in order to evaluate the active oxygen ratio in the glass, a specific ratio X=(R2O+R'O-P2O5-Al2O3-B2O3) / (SiO2+P2O5+Al2O3+B2O3) is specified. This means that the active oxygen increases as the value of X increases. That is, if X is larger, it means that there is more active oxygen. If X>0, it means that there is enough active oxygen in the glass substrate, and the glass substrate, especially the glass surface, is active. In short, when X>0, there are enough non-bonded oxygen ions on the glass surface, and the active oxygen easily reacts with moisture in the air to form [OH-] groups. The active [OH-] group is beneficial to increase the wettability between the glass substrate 2 and the microstructure layer 3 (i.e., the polymer), and reduce the contact angle between the glass substrate 2 and the microstructure layer 3. Active oxygen and active [OH-] groups can improve the surface adhesion ability of the glass substrate.
[0052] It is found from experiments that if the X value of the glass is low, for example X≤-0.2, it means that all oxygen is bonded to glass former cations (such as Si, Al, B, P), and the glass is an inlay. In this case, sufficient [OH-] cannot be formed on the glass surface. In addition, it is found that if the glass has a high X value, for example X≥-0.2, it results in sufficient active [OH] groups on the glass surface and a small wetting contact angle with the glue on the glass substrate. This special property is conducive to the application of glass in wafer-level optical devices and diffractive optical elements. According to the present invention, the ratio X of the glass substrate is ≥-0.2, preferably ≥0, and more preferably ≥0.2.
[0053] In order to provide a higher NBO value, in the present invention, the glass contains the following oxide-based components in mol %:
[0054]
[0055] The glasses used in the present invention, in particular the glasses described above, can also be modified. For example, the color can be changed by adding transition metal ions, rare earth ions such as Nd2O3, Fe2O3, CoO, NiO, V2O5, MnO2, TiO2, CuO, CeO2, Cr2O3 and 0-2 wt. % of As2O3, Sb2O3, SnO2, SO3, Cl, F, and / or CeO2 to the glass composition.
[0056] By containing K + 、Na + 、Ag + Salt bath or Cu 2+ The glass products can also have antimicrobial function or chemical toughening effect by ion exchange in a salt bath. + Cu 2+ The concentration is higher than 1 ppm, preferably higher than 100 ppm, more preferably higher than 1000 ppm.
[0057] Due to its performance requirements, the micro-optical element 1 requires high reliability and high optical efficiency. In order to meet these requirements, high bonding must be achieved between the glass substrate 2 and the microstructure layer 3. To ensure this, the glass substrate 2 should have specific geometrical properties, such as surface roughness, total thickness variation (TTV) and warpage, and coefficient of thermal expansion (CTE). These properties may affect the bonding reliability between the glass substrate and the microstructure layer.
[0058] In the present invention, the total thickness variation of the glass substrate 2 is TTV≤40 μm, preferably TTV≤30 μm, more preferably TTV≤20 μm, and most preferably TTV≤10 μm. In this case, due to the low TTV, the microstructure layer 3 uniformly contacts the surface of the glass substrate 2, and the bonding between the microstructure layer 3 and the glass substrate 2 is increased.
[0059] In addition, in order to improve the bonding strength between the glass substrate and the microstructure layer, the 2 When the local thickness variation of the glass substrate is LTV≤5μm, preferably LTV≤1μm, more preferably LTV≤0.5μm, and most preferably LTV≤0.1μm, this is because LTV affects the bonding strength between the glass substrate and the microstructure layer in the same way as TTV.
[0060] In addition, the thickness tolerance of the glass substrate is δ≤80 μm, preferably δ≤50 μm, and more preferably δ≤20 μm. In one embodiment, the ratio of the tolerance to the thickness of the glass substrate is less than 10%, preferably less than 8%, and more preferably less than 5%. Since the thickness tolerance δ and the ratio of the tolerance to the thickness are very low, the light incident on the micro-optical element can be uniformly transmitted through the glass substrate, thereby improving the imaging quality.
[0061] In order to further improve the bonding strength between the glass substrate and the microstructure layer, the warpage of the glass substrate is ≤200 μm, preferably ≤100 μm, more preferably ≤80 μm, and most preferably ≤50 μm. In this case, the glass substrate can be substantially parallel to the microstructure layer, which can improve the uniform bonding strength between the glass substrate 2 and the microstructure layer 3. In addition, this can also improve the quality of the micro-optical element in terms of light transmittance or reflectivity as required.
[0062] In order to further improve the bonding strength between the glass substrate and the microstructure layer, the surface roughness of the glass substrate 2 of the present invention is Ra≤20 nm, preferably Ra≤10 nm, and more preferably Ra≤5 nm.
[0063] According to the optical requirements of the micro-optical element, the glass substrate 2 should exhibit certain optical properties. In another preferred embodiment, the refractive index n of the glass substrate 2 is d In this case, the refractive index n listed above is in the range of 1.4 to 2.5, preferably in the range of 1.5 to 2.3, and more preferably in the range of 1.8 to 2.0. d The glass substrate can be used for optical applications because it matches the existing polymer used for the microstructure layer. In a preferred embodiment, the refractive index n between the glass substrate and the microstructure layer is d The difference Δn d Less than 0.5.
[0064] According to the optical requirements of the micro-optical element, the transmittance of the glass substrate 2 at a wavelength ranging from 400 to 1500 nm is T≥90%, preferably T≥91%, and more preferably T≥92%. In this embodiment, the glass substrate can be used in optics, especially in the field of 3D imaging and sensing.
[0065] In order to reduce the peeling of the microstructure layer 3 from the glass substrate 2 when subjected to thermal shock, the thermal expansion coefficient CTE of the glass substrate 20-300℃ The coefficient of thermal expansion (CTE) of the glass substrate should not be too different from that of the microstructure layer. Under ideal conditions, the CTE of the glass substrate is substantially equal to the CTE of the microstructure layer. In this case, when the micro-optical element is subjected to thermal shock, the glass substrate and the microstructure layer expand similarly and no displacement occurs between them. In one embodiment of the present invention, the CTE of the glass substrate is 20-300℃ ≤15×10 -6 / K, optimal CTE 20-300℃ ≤12×10 -6 / K.
[0066] In addition, the bonding strength between the glass substrate and the microstructure layer is a key requirement for micro-optical elements by using, for example, nanoimprinting technology. Debonding is always a problem and concern. The present invention aims to provide a glass substrate with suitable surface properties, such as high surface tension, low surface tension ratio between the glass substrate and the microstructure layer, and a certain amount of NBO to increase the glass surface tension and surface wettability, which helps to improve the bonding strength between the glass substrate and the microstructure layer. It has been found that higher surface tension leads to a smaller water / glue contact angle, which increases the surface adhesion ability of the glass substrate.
[0067] Example:
[0068] Table 1 shows several examples of glass substrates according to the present invention.
[0069]
[0070] R is an alkali metal, including Li, Na, and K;
[0071] R' is an alkaline earth metal including Mg, Ca, Ba; and
[0072] R" includes Ti and Zr, but does not include Si.
[0073] From the table above, taking the glass of Example 2 as an example, the glass provides a large amount of NBO (eg, 1.16), thus providing a higher ratio X = -0.11. In this case, it will attract more OH- on the glass surface and lead to better liquid wettability.
[0074] In detail, referring to FIG. 4A to FIG. 4C , the glue contact angles of the glass are shown with respect to Example 2, Example 5, and Example 3, respectively, and the glue contact angles thereof are 10.8°, 11.2°, and 11.3°, respectively. Figure 7 , the bonding strength between the glass substrate and the microstructure layer is 7MPa, 6MPa and 5MPa.
[0075] Figure 2 and Figure 3 The relationship between the glue contact angle and the values of NBO and X is shown respectively. From these two figures, it can be determined that the higher the values of NBO and X, the smaller the glue contact angle, which in turn improves the bonding strength and stability of the glass substrate 2 and the microstructure layer 3.
[0076] Figure 5A and Figure 5B A schematic diagram showing free radicals used to bond on one surface of glass. Figure 5A A schematic diagram is shown for free radicals bonding on one surface of glass, with a low NBO value and with less active oxygen on the glass surface. Figure 5BA schematic diagram is shown for free radicals bonding on one surface of glass, with a high NBO value and more active oxygen on the glass surface.
[0077] Figure 7 The principle of the reaction of glass with a microstructure layer such as a polymer is shown. In this figure, it is also shown that a higher [OH-] content on the glass will generate more active oxygen on the glass surface and make the glass surface more active, thereby making the bond between the glass and the microstructure layer stronger.
[0078] According to the present invention, the bonding strength between the glass substrate and the microstructure layer is greater than 0.5 MPa, preferably greater than 1 MPa, and more preferably greater than 1.5 MPa.
[0079] In another aspect of the present invention, a method for manufacturing the above-mentioned micro-optical element is provided. The method comprises the following steps:
[0080] (a) A polymer is deposited onto a substrate and a UV-transparent template is placed on top.
[0081] (b) The template is pressed into the polymer and the polymer is cured by irradiating the template with ultraviolet light.
[0082] (c) The template is released, leaving the cured polymer with the imprinted features, i.e., the microstructured layer.
[0083] In one embodiment, the microstructure layer 3 is made of modified epoxy resin, for example OM614. In this case, when curing the microstructure layer 3 in step c), UV light with a wavelength in the range of 320 to 380 nm is used. In short, the curing will be at 25 mW / cm 2 After curing, the micro-optical element was annealed at 120°C for 1 hour.
[0084] The glass according to the present invention shows a large amount of NBO, and therefore, the glass has more negatively charged oxygen. A higher number of NBO or more active oxygen can generate a highly active glass surface, and at the same time can increase the wettability of the glass surface and reduce the water / glue contact angle. Good glass surface wettability and low water / glue contact angle are beneficial to the bonding strength of glass and glue (i.e., microstructure layer).
Claims
1. A micro-optical element, comprising: A glass substrate, wherein the thickness of the glass substrate is t≤1500 μm; as well as a microstructure layer formed of a polymer imprinted on the glass substrate; wherein the bonding strength between the microstructure layer and the glass substrate is greater than 0.5 MPa; The total thickness variation TTV of the glass substrate is ≤40 μm; The thickness tolerance of the glass substrate is δ≤80 μm, Characterized in that the glass substrate has a specific amount of non-bridging oxygen NBO≥0.3, Where NBO=(R2O+R'O) / (P2O5+Al2O3+B2O3+TiO2+ZrO2); and / or The ratio X = (R2O + R'O-P2O5-Al2O3-B2O3) / (SiO2 + P2O5 + Al2O3 + B2O3) is greater than -0.2, Wherein R is an alkali metal, including Li, Na, and K; R' is an alkaline earth metal, including Mg, Ca, and Ba.
2. The micro-optical element according to claim 1, characterized in that: The thickness of the glass substrate is t≤1200 μm, the bonding strength between the microstructure layer and the glass substrate is greater than 1 MPa, the total thickness variation TTV of the glass substrate is ≤30 μm, and the thickness tolerance of the glass substrate is δ≤50 μm.
3. The micro-optical element according to claim 1, characterized in that: The thickness of the glass substrate is t≤1100 μm, the bonding strength between the microstructure layer and the glass substrate is greater than 1.5 MPa, the total thickness variation TTV of the glass substrate is ≤20 μm, and the thickness tolerance of the glass substrate is δ≤20 μm.
4. The micro-optical element according to claim 1, characterized in that: The total thickness variation TTV of the glass substrate is ≤10 μm, and the thickness tolerance of the glass substrate is δ ≤10 μm.
5. The micro-optical element according to claim 1, characterized in that: The total thickness variation TTV of the glass substrate is ≤5 μm, and the thickness tolerance of the glass substrate is δ ≤5 μm.
6. The micro-optical element according to claim 1, characterized in that: The thickness tolerance of the glass substrate is δ≤2 μm.
7. The micro-optical element according to any one of claims 1 to 6, characterized in that NBO ≥ 0.5; and / or Ratio X is greater than 0; The glass substrate has a low adhesive contact angle θg of less than 35°. and / or The warpage of the glass substrate is ≤500 μm, and / or The ratio of TTV of the glass substrate to glass thickness is less than 10%.
8. The micro-optical element according to any one of claims 1 to 6, characterized in that NBO ≥ 1; and / or The ratio X is greater than 0.2; The glass substrate has a low adhesive contact angle θg of less than 25°. and / or The warpage of the glass substrate is ≤100 μm, and / or The glass substrate has a ratio of TTV to glass thickness of less than 8%.
9. The micro-optical element according to any one of claims 1 to 6, characterized in that NBO ≥ 1.5; and / or The low glue contact angle θg of the glass substrate is less than 15°, and / or The warpage of the glass substrate is ≤80 μm, and / or The ratio of TTV to glass thickness of the glass substrate is less than 5%.
10. The micro-optical element according to any one of claims 1 to 6, characterized in that NBO ≥ 2; and / or The warpage of the glass substrate is ≤50 μm.
11. The micro-optical element according to any one of claims 1 to 6, characterized in that The surface roughness of the glass substrate Ra is less than or equal to 20 nm.
12. The micro-optical element according to any one of claims 1 to 6, characterized in that The surface roughness of the glass substrate Ra is less than or equal to 10 nm.
13. The micro-optical element according to any one of claims 1 to 6, characterized in that: The surface roughness of the glass substrate Ra is less than or equal to 5 nm.
14. The micro-optical element according to any one of claims 1 to 6, characterized in that: The glass comprises the following compositions in mol % based on oxides:
15. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.4 to 2.
5.
16. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.45 to 1.
55.
17. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.41 to 2.
1.
18. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.42 to 2.
0.
19. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.45 to 1.
9.
20. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.45 to 1.
8.
21. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.45 to 1.
7.
22. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n of the glass substrate d In the range of 1.45 to 1.
6.
23. The micro-optical element according to any one of claims 1 to 6, characterized in that The transmittance T of the glass substrate is ≥90%.
24. The micro-optical element according to any one of claims 1 to 6, characterized in that The transmittance T of the glass substrate is ≥91%.
25. The micro-optical element according to any one of claims 1 to 6, characterized in that The thermal expansion coefficient CTE of the glass substrate 20-300℃ ≤15×10 -6 / K.
26. The micro-optical element according to any one of claims 1 to 6, characterized in that The thermal expansion coefficient CTE of the glass substrate 20-300℃ ≤10×10 -6 / K.
27. The micro-optical element according to any one of claims 1 to 6, characterized in that CTE of the glass substrate 玻璃 The CTE of the microstructure layer 聚合物 Ratio of CTE 聚合物 / CTE 玻璃 ≤100.
28. The micro-optical element according to any one of claims 1 to 6, characterized in that CTE of the glass substrate 玻璃 The CTE of the microstructure layer 聚合物 Ratio of CTE 聚合物 / CTE 玻璃 ≤80.
29. The micro-optical element according to any one of claims 1 to 6, characterized in that The refractive index n between the glass substrate and the microstructure layer d The difference Δn d ≤0.
5.
30. The micro-optical element according to any one of claims 1 to 6, characterized in that The glass substrate is made of a glass selected from the group consisting of silicate glass, borosilicate glass, aluminosilicate glass, aluminoborosilicate glass, soda-lime glass, and lithium aluminosilicate glass.
31. The micro-optical element according to any one of claims 1 to 6, characterized in that The microstructure layer is composed of a polymer of epoxy resin or acrylic resin.
32. A method for producing a micro-optical element according to any one of claims 1 to 31, characterized in that The method comprises the following steps: - providing a glass substrate, wherein the thickness of the glass substrate is t≤1500 μm, wherein the total thickness variation TTV of the glass substrate is ≤40 μm; and the thickness tolerance of the glass substrate is δ≤80 μm; wherein: The glass substrate has a specific number of non-bridging oxygen NBO≥0.3, where NBO=(R2O+R'O) / (P2O5+Al2O3+B2O3+TiO2+ZrO2); and / or The ratio X = (R2O + R'O-P2O5-Al2O3-B2O3) / (SiO2 + P2O5 + Al2O3 + B2O3) is greater than -0.2, wherein R is an alkali metal, including Li, Na, K; R' is an alkaline earth metal, including Mg, Ca, Ba; and - applying a microstructured polymer layer to the glass substrate to form a microstructured layer.
33. The method according to claim 32, characterized in that The thickness of the glass substrate is t≤1200 μm, wherein the total thickness variation TTV of the glass substrate is ≤30 μm; and the thickness tolerance of the glass substrate is δ≤50 μm.
34. The method according to claim 32, characterized in that The thickness of the glass substrate is t≤1100 μm, wherein the total thickness variation TTV of the glass substrate is ≤20 μm; and the thickness tolerance of the glass substrate is δ≤20 μm.
35. The method according to claim 32, characterized in that The total thickness variation TTV of the glass substrate is ≤10 μm; and the thickness tolerance of the glass substrate is δ ≤10 μm.
36. The method according to claim 32, characterized in that The total thickness variation TTV of the glass substrate is ≤5 μm; and the thickness tolerance of the glass substrate is δ ≤5 μm.
37. The method according to claim 32, characterized in that The thickness tolerance of the glass substrate is δ≤2 μm.
38. The method according to any one of claims 32 to 37, characterized in that The microstructured polymer layer can be applied uniformly by spin coating, spray coating or deposition, and / or Applying the microstructured polymer layer to the glass substrate comprises the following steps: (a) A polymer is deposited on a substrate and a UV-transparent template is placed on top; (b) pressing the template into the polymer layer and curing; and (c) releasing the template, leaving behind a cured polymer with the embossed features to form a microstructure layer.
39. The method according to claim 38, characterized in that The microstructure layer can be cured by UV or thermal heating.
40. The method according to any one of claims 32 to 37, characterized in that The microstructure layer can be applied to both sides of the glass substrate.
41. Use of a micro-optical element according to any one of claims 1 to 31, wherein the micro-optical element is used in diffractive optical elements, refractive lenses, mirrors, prisms, GRIN lenses, hybrid elements, diffusers in 3D imaging / sensors, augmented reality, virtual reality, cameras, automated manufacturing systems, mobile communications.
Citation Information
Patent Citations
Method for producing glass base laminated body, method for manufacturing optical element, optical element and concentrator photovoltaic system
EP3093139A1
Photocurable resin composition and optical component using the same
JP2011021177A
Microstructured light guide plates and devices comprising the same
WO2018094017A1